2006
DOI: 10.1158/1535-7163.mct-06-0235
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic synergy between the multikinase inhibitor sorafenib and the proteasome inhibitor bortezomib in vitro: induction of apoptosis through Akt and c-Jun NH2-terminal kinase pathways

Abstract: This study was undertaken to characterize preclinical cytotoxic interactions for human malignancies between the multikinase inhibitor sorafenib (BAY 43-9006) and proteasome inhibitors bortezomib or MG132. Multiple tumor cell lines of varying histiotypes, including A549 (lung adenocarcinoma), 786-O (renal cell carcinoma), HeLa (cervical carcinoma), MDA-MB-231 (breast), K562 (chronic myelogenous leukemia), Jurkat (acute T-cell leukemia), MEC-2 (B-chronic lymphocytic leukemia), and U251 and D37 (glioma), as well … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
65
0
2

Year Published

2008
2008
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(76 citation statements)
references
References 40 publications
9
65
0
2
Order By: Relevance
“…Moreover, Tan IIA treatment led to a concentration-dependent increase in the levels of p53, paralleling the accumulation of p21. These results suggest that the observed p21 accumulation may be due to p53 activation, since p53 (wild-type) upregulates p21 expression (16). It should be noted that it is possible that the level of p21 was altered via a p53-independent pathway.…”
Section: Discussionmentioning
confidence: 74%
“…Moreover, Tan IIA treatment led to a concentration-dependent increase in the levels of p53, paralleling the accumulation of p21. These results suggest that the observed p21 accumulation may be due to p53 activation, since p53 (wild-type) upregulates p21 expression (16). It should be noted that it is possible that the level of p21 was altered via a p53-independent pathway.…”
Section: Discussionmentioning
confidence: 74%
“…This may certainly depend on the drugpartner combined with sorafenib. A synergism between sorafenib and bortezomib has been demonstrated in the CLL cell line MEC-2 30 , but it still needs to be experimentally explored whether this can be translated to primary CLL cells.…”
Section: Discussionmentioning
confidence: 99%
“…68,94 Interaction between inhibitors of the proteasome and HDAC inhibitors have been investigated, showing synergistic effect, in different types of cancer and future clinical applications of this combination should be considered. [95][96][97][98][99] Synergistic effects were shown for BZ in combination with tubacin and SAHA that inhibits HDAC6 resulting in a marked accumulation of ubiquitinated proteins. 100,101 Moreover, recent studies showed that disruption of autophagy, resulted in accumulation of ubiquitinated proteins and HDACs inhibitors, like Vorinostat, potentiates aggregates formation, super oxide generation and apoptosis.…”
Section: Histone Deacetylase Inhibitorsmentioning
confidence: 99%
“…100,101 Moreover, recent studies showed that disruption of autophagy, resulted in accumulation of ubiquitinated proteins and HDACs inhibitors, like Vorinostat, potentiates aggregates formation, super oxide generation and apoptosis. 96,98,102,103 …”
Section: Histone Deacetylase Inhibitorsmentioning
confidence: 99%